(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: The most common human bacterial disease is likely to be the Helicobacter pylori. H. pylori is known as Campylobacter pyloridis, and it is prevalent among children, and genetically shown to be inherited in families. H. pylori This is a e-proteobacterium that inhabits the human stomach in patches and in the antrum rather than fundus. H. pylori is a very successful pathogen with an estimated 50 percent of the population in the world infected. H. pylori infection commonly varies according to the region, socioeconomic status, and age. Objective: The objective of this review to understand that how Helicobacter pylori cause gastric ulcer at the molecular level. Methodology: The Molecular mechanism of Helicobacter pylori pathogenesis in gastric ulcer involves virulence factors like CagA and VacA. These factors disrupt gastric epithelial cell function and trigger inflammation. Genetic and epigenetic factors also contribute to susceptibility and disease outcome. The review of studies shows that H. pylori pathogenesis in gastric ulcer is mainly driven by its major virulence factors CagA and VacA, which disrupt epithelial signaling and induce cellular damage. The bacterium’s motility, adhesion proteins, and urease activity further enhance survival and chronic colonization. These mechanisms collectively trigger strong inflammatory responses, leading to mucosal injury and ulcer formation. Conclusion: H. pylori cause gastric ulcers through a combination of toxin-mediated epithelial damage and persistent inflammation. Its virulence factors, especially CagA and VacA, play a central role in disrupting mucosal integrity. Overall, long-term colonization and sustained inflammatory signaling lead to progressive ulcer formation.